2010
DOI: 10.1007/s11426-010-0126-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humic acids and microorganisms on decabromodiphenyl ether, 4,4′-dibromodiphenyl ether and anthracene transportation in soil

Abstract: In this study, effects of humic acids (HA) and microorganisms on the migration of hydrophobic organic contaminants (HOCs), decabromodiphenyl ether (BDE-209), 4,4′-dibromodiphenyl ether (BDE-15) and anthracene, in soils were examined. More soil particles were dispersed into the colloidal phase (0.22-1 m) in the presence of HA and/or microorganisms as a result of increased erosion and friction. The study suggested that PBDEs (BDE-209 and BDE-15) and anthracene in soils would be transported to other places by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…So in our papers Zhang et al, 2011) the purity of BDE-209 was given as >98%. Additionally, we also noted that the purity of >98% BDE-209 in this commercial product has also been reported by other researchers (Deng et al, 2011;Yu et al, 2010). During our sample preparation the photolytically induced debromination of BDE-209 was avoided by some precautions such as that the samples were covered with aluminum foil and kept in the dark place when the samples were temporarily stored.…”
Section: Response To the Letter From Biesemeier Et Alsupporting
confidence: 85%
“…So in our papers Zhang et al, 2011) the purity of BDE-209 was given as >98%. Additionally, we also noted that the purity of >98% BDE-209 in this commercial product has also been reported by other researchers (Deng et al, 2011;Yu et al, 2010). During our sample preparation the photolytically induced debromination of BDE-209 was avoided by some precautions such as that the samples were covered with aluminum foil and kept in the dark place when the samples were temporarily stored.…”
Section: Response To the Letter From Biesemeier Et Alsupporting
confidence: 85%
“…So in our article the purity of BDE-209 was given as >98% [2]. In addition, we also noted that the purity of >98% BDE-209 in this commercial product has also been reported by other researchers [3,4].…”
supporting
confidence: 78%
“…Influent tank (ng) 300.3 ± 2.3 300.2 ± 1.8 300.5 ± 2.1 0.0-50.0-cm island (ng) 618.9 ± 7.5 666.9 ± 7.1 679.7 ± 6.6 Effluent tank (ng) 158.9 ± 4.3 112.1 ± 3.8 99.7 ± 4.8 Sum (ng) 1078.1 ± 8.9 1079.2 ± 8.3 1079.9 ± 8.4 Initial addition (ng) 1080.2 ± 3.2 1080.7 ± 2.4 1080.2 ± 2.7 Sum/initial addition (%) 99.8 ± 0.4 99.9 ± 0.7 99.8 ± 0.6 in Table 4. It was indicated that naphthalene in complexes would undergo both the chemo-and bio-chemo-degradation and evaporation into the atmosphere because of the values of the log K OW and log K OC of naphthalene by nature (Yu et al 2010;Simarro et al 2011;Rao et al 2014).…”
Section: Wp1mentioning
confidence: 99%
“…It was known that the results of colloid transport behaviors in waters were not much clearer due to the complex constituents and structures (Yu et al 2010;Alem et al 2015). Naphthalene behaviors in waters were less detailed because of its properties by nature.…”
Section: Capture Behaviors Of Floating Island On Both Naphthalene Andmentioning
confidence: 99%
See 1 more Smart Citation